Diagnosing And Mitigating Employee Turnover: A Case Study on Quality of Work Life - Ramot, Timotius; Pratama, Andika Putra (PT. EQUATOR SINAR AKADEMIA, 2025)
Employee turnover is a critical issue in the manufacturing sector, leading to increased operational costs, workflow disruptions, and reduced productivity. This study investigates the relationship between Quality of Work Life (QoWL) and employee turnover in XYZ Company, a furniture manufacturing company, with a particular focus on the production division. The company faces a high turnover rate of 17.70%, with the production division contributing 92.11% of total employee exits. This research employs a quantitative approach, utilizing QoWL and turnover intention questionnaires to assess key factors such as working structure, compensation, work environment, and interpersonal relationships. Data were collected from production employees and analyzed using correlation tests and multiple linear regression to determine the impact of QoWL dimensions on turnover intention. The findings reveal that dissatisfaction with compensation and inadequate working conditions are the primary drivers of turnover. A strong correlation was identified between QoWL dimensions and turnover intention, highlighting the urgency for targeted interventions. The study proposes practical solutions, including aligning compensation with industry standards, implementing structured career development programs, and enhancing workplace conditions to improve employee retention. By addressing QoWL dimensions, organizations can foster a supportive work environment, enhance job satisfaction, and reduce turnover rates, ultimately ensuring long-term operational stability and success.